Hubungan antara Persepsi Manajemen Lini terhadap Turnover di Manajemen Puncak dengan Komitmen Organisasi - Susatyo Yuwono; Yadi Purwanto; Ade Kurniawan (Jurnal Siasat Bisnis, 2006)
This research’s aim is to find the correlation between line management’s perception about top management’s turnover and organizational commitment. The hypotesis is there is a correlation between line management’s perception about top management’s turnover and organizational commitment. Population, as subject, are 37 line management’s of PT Krakatau Engineering,. Data gathered by questionnaires: line management’s perception about top management’s turnover, and organizational commitment.The analysis by product moment techniques, and the results shows correlation index (r) = 0,584, p < 0,01. It means there is a positive very significant correlation between line management’s perception about top management’s turnover and organizational commitment. Keyword: perception on turnover, organizational commitment